47 A review of patients with heart failure with mid-range ejection fraction (HFmrEF): co-morbidities and outcomes. (30th September 2020) - O' Callaghan, D; Wheen, P; Murray, P; Minelli, C; Daly, C
Abstract : Background: The ESC now recognises HF patients with a left ventricular ejection fraction (LVEF) of 40%-49% as having a distinct phenotype, referred to as Heart Failure with mid-range Ejection Fraction (HFmrEF). This classification was implemented to promote research in this group of heart failure (HF) patients. Aims: We aimed to compare the co-morbidities of HFmrEF patients with those of Heart Failure with preserved Ejection Fraction (HFpEF) and Heart Failure with reduced Ejection Fraction (HFrEF) patients, and aimed to compare hospitalisations for acute decompensation HF, and mortality between these groups. Methods: All new referrals to a HF clinic in three neighbouring hospitals were included between January 1st 2017, and December 31st 2017. Data was collected on co-morbidities associated with each HF classification. Mean follow up was 17.5 months (± 7.6) and we recorded hospitalisations for ADHF and mortality data. Results: 286 new patients were referred to one of our 3 HF clinics; following optimisation, the patients were divided as: HFpEF 67 (23.4%), HFmrEF 58 (20.3%), HFrEF 94 (32.9%). 69 patients did not have a repeat echocardiogram. Table 1 presents the co-morbidities. Categorical data was analysed with Chi-square testing and continuous data analysed with unpaired t testing. Significance in HFrEF and HFpEF is in comparison with HFmrEF. Figure 1 is a Kaplan Meier curve demonstrating the events across the follow-up period. Conclusion: Co-morbidities were similar in HFmrEF as compared with HFpEF and HFrEF, aside from previous CABG surgery (fewer in HFmrEF as compared with HFpEF and HFrEF) and HTN (there were more in HFpEF). Mortality was similar across the 3 groups over our follow up period of 17.5 months, and there was no difference in mean hospitalisations for ADHF between the groups. In our catchment area, our HFmrEF have a similar phenotype to our HFpEF and HFrEF cohorts.